Promotion management : a strategic approach - Burnett, John J. (St. Paul : West Publishing Company, 1984)
Promotion Management: A Strategic Approach, attempts to deliver what the title suggests. The philosophy of this basic textbook is to provide the reader with a comprehensive understanding of the total promotional effort including the process that begins with the delineation of objectives and ends with measures of effectiveness. In addition, the many controllable and uncontrollable factors that influence this process are introduced. A necessary caveate is that, although a normative approach is used in this book, in fact most companies must be satisfied with a promotional effort that falls short of the ideal. For many companies there tends to be a strong emphasis on either personal selling or advertising, with sales promotion and public relations taking minor roles. It is only the large or very insightful companies that appear to be able and willing to employ a comprehensive promotion strategy.
1. Promotion: General Considerations -- 2. The Role of Promotional Strategy in Marketing -- 3. The Marketing Environment: A Marco Perspective -- 4. The Marketing Environment: A Micro Perspective -- 5. The Role of Promotion in the Marketing Mix -- 6. market Segmentation -- 7. Posting -- 8. The Role Of Resellers in promotion -- 9. Advertising: Its Background and Structure -- 10. The Advertising Campaign: The Planned Creative Process -- 11. Advertising Media -- 12. Developing the Media Plan -- 13. Sales Promotion -- 14. Public Relations -- 15. The management of Personal Selling -- 16. The Personal Selling Process -- 17. Measuring Promotional Performance -- 18. Developing a Promotion Budget -- 19. Legal Consideration in promotion -- 20. The Role of Promotion in the Future.
Includes index.
Keywords: SALES PROMOTION; CONSUMERS -- PSYCHOLOGY